Infrastructure ecology: an evolving paradigm for sustainable urban development. (1st October 2017) - Pandit, Arka; Minné, Elizabeth A.; Li, Feng; Brown, Hillary; Jeong, Hyunju; James, Jean-Ann C.; Newell, Joshua P.; Weissburg, Marc; Chang, Michael E.; Xu, Ming; Yang, Perry; Wang, Rusong; et al.
Abstract: Increasing urbanization places cities at the forefront of achieving global sustainability. For cities to become more sustainable, however, the infrastructure on which they rely must also become more productive, efficient and resilient. Unfortunately the current paradigm of urban infrastructure development is fragmented in approach lacking a systems perspective. Urban infrastructure systems are analogous to ecological systems because they are interconnected, complex and adaptive components that exchange material, information and energy among themselves and to and from the environment, and exhibit characteristic scaling properties that can be expressed by Zipf's Law. Analyzing them together as a whole, as one would do for an ecological system, provides a better understanding about their dynamics and interactions, and enables system-level optimization. The adoption of this " infrastructure ecology " approach will result in urban (re)development that requires lower investment of financial and natural resources to build and maintain, is more sustainable (e.g. uses less materials and energy and generates less waste) and resilient, and enables a greater and more equitable opportunities for the creation of wealth and comfort. The 12 guiding principles of infrastructure ecology will provide a set of goals for urban planners, engineers and other decision-makers in an urban system for urban (re)development. Graphical abstract: Highlights: Infrastructure ecology, a novel paradigm for urban infrastructure development is presented. Urban infrastructure systems function analogous to natural ecological systems. Interdependence between infrastructure sectors are identified and assessed. Infrastructural symbiosis reorganizes the flows within for system-level optimization. 12 guiding principles of infrastructure ecology are presented for decision makers.